2009
DOI: 10.1097/icu.0b013e32832a7ded
|View full text |Cite
|
Sign up to set email alerts
|

Corneal multifocality with excimer laser for presbyopia correction

Abstract: The level of scientific evidence from the literature is enough to consider that presbyLasik is a useful tool in the correction of presbyopia. However, most of the techniques are still under development in clinical investigations and further clinical data will validate the outcomes reported for the different techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 27 publications
1
43
1
2
Order By: Relevance
“…In conventional monovision LASIK, the dominant eye is targeted for Plano refraction for good distance vision while the non-dominant eye is targeted to −1.50 D for good near vision [1, 2]. More advanced laser algorithms have been developed to produce a multifocal ablation or manipulate asphericity to improve near vision [3–9]. …”
Section: Introductionmentioning
confidence: 99%
“…In conventional monovision LASIK, the dominant eye is targeted for Plano refraction for good distance vision while the non-dominant eye is targeted to −1.50 D for good near vision [1, 2]. More advanced laser algorithms have been developed to produce a multifocal ablation or manipulate asphericity to improve near vision [3–9]. …”
Section: Introductionmentioning
confidence: 99%
“…Peripheral presbyLASIK removes an important amount of corneal tissue especially in the myopes, making this a limitation of the technique [6]. Central presbyLASIK can be performed in either myopes or hyperopes as the amount of tissue necessary for removal is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Gobien et al reported an improvement of 1 line of near UCVA in hyperopic presbyopes [5]. There are very few reports on this technique and it was not well accepted by surgeons because it induced significant levels of vertical coma [6]. …”
Section: Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches in order to achieve a functional vision for all distances as if we had again 20 [19][20][21][22][23][24][25][26][27][28], Scleral Ciliary Surgery [29], corneal inlays [30][31][32], monovision [33,34] and accommodative intraocular lenses [35,36]. In this summary a description of the accommodative intraocular lenses (AIOLs) is presented.…”
Section: Introductionmentioning
confidence: 99%